The GENESTAR manual for biospecimen collection biobanking and omics data generation from commercial space missions - Aparna Krishnavajhala; Marie-Claude Gingras; Emmanuel Urquieta; Hsu Chao; Dilrukshi Bandaranaike; Yi Chen; Sravya Bhamidipati; Viktoriya Korchina; S. Michelle Griffin; Michal M. Masternak; Hannah Moreno; Javid Mohammed; et al. (npj Microgravity)
Abstract The surge in commercial and civilian spaceflight enables the systematic and longitudinal, large-scale biospecimen collection to understand the prospective effects of space travel on human health. The Genomics and Space Medicine (Space Omics) project at BCM-HGSC involves a comprehensive biospecimen collection plan from commercial/private space flight participants. The manuscript addresses the critical gaps in the biospecimen collection process including details of the informed consent process, a provision for subjects to obtain custom CLIA-WGS reports, a data dictionary and a LIMS enabled biobank. The manuscript also discusses the biospecimens collection, processing methodologies and nucleic acid suitability for Omics data generation. Results from Axiom-2 mission where, 339 biospecimens were collected using ‘Genomic Evaluation of Space Travel and Research (GENESTAR)’ manual, at two different sites, showed that 98% of the blood samples and 91.6% of the non-blood samples passed the QC requirements for Omics assays, underscoring the reliability and effectiveness of the GENESTAR manual.